Prof. Mitsunori Kirihata: concentrating on boron chemistry, promoting the development of boron neutron capture therapy - Cheung, Mike (Therapeutic Radiology and Oncology, 2018)
The 3rd Annual Academic Conference of Taiwan Society of Neutron Capture Therapy [Jointly with the 10th Trilateral boron neutron capture therapy (BNCT) meeting between Taiwan and Japan] was successfully held on 27 January, 2018 at Taipei Medical University.